The Effect Of Fingerprint Attendance and Work Motivation On Employee Discipline On CV Story Of Copyright - Sam Cay; Dewi Sartika; Raden Yati Sumiaty; Ani Meryanti; Denok Sunarsi (Jurnal Office, 2021)
This study aims to determine the effectiveness of the application of attendance (fingerprint) in improving employee discipline at the CV Hikayat Cipta Semesta office. This study uses a quantitative research type where there are two variables, namely fingerprint attendance and works motivation as independent variables and employee discipline as the dependent variable, using data sources including primary, secondary, population, and sample data. . Data collection methods used are interviews, distributing questionnaires to several respondents and documenting data or variables in the form of notes, and so on. As well as using measuring tools in the form of validity and reliability to see the validity and reliability of the research results in Cronbach alpha, then using data analysis methods using multiple regression analysis methods which are used to determine the effect of the independent variable and the dependent variable partially and simultaneously, namely the fingerprint attendance variable. From the results of this study, it was seen partially with the T-test that fingerprint attendance did not significantly affect employee discipline at CV Hikayat Cipta Semesta, while the work motivation variable had a significant effect on employee discipline at CV Hikayat Cipta Semesta. Furthermore, the simultaneous influence test with the F test, shows that fingerprint attendance and work motivation have a significant effect on employee discipline. From the results of this research, it is hoped that it can be useful for all parties, especially in improving employee discipline.